The Influence of Independent Curriculum Management on Organizational Culture and Positive School Culture Research on Integrated Islamic Elementary Schools in Purwakarta District - Iwan Setiawan; Linda Tazkiyatul Munawaroh; Irawan (Yayasan Mentari Madani, 2023)
The educational process basically aims to improve the overall quality of human life. It can also be interpreted as a means of passing on culture through the transmission of certain information, utilizing mental processes and rationality to gain experience and develop abilities and a sense of dignity through the acquisition of knowledge and skills. The Freedom of Learning initiative was introduced by Nadiem Makarim Anwar, Minister of Education and Culture. This policy was implemented in response to the recognition that education in Indonesia has not paid enough attention to quality aspects. The research conducted for this initiative uses a quantitative approach rooted in the positivistic paradigm. A quantitative approach is a research methodology rooted in positivism, which is used to investigate a specific population or sample. Data collection in this approach involves the use of research instruments, whereas data analysis is mostly quantitative and statistical in nature, with the main objective of testing pre-established hypotheses. In the context of the Integrated Madrasah Ibtidaiyah in Purwakarta Regency, it is known that the Principal's Leadership, Organizational Culture, and Work Motivation together have a significant influence on teacher performance, accounting for 87.00% of the total impact. The remaining 13.00% was associated with other variables that were not studied in this study but were known to affect teacher performance.